Understanding adherence to treatment and physical activity in children with hemophilia: The role of psychosocial factors. (2nd January 2017) - Bérubé, Sarah; Cloutier-Bergeron, Audrey; Amesse, Claudine; Sultan, Serge
ABSTRACT: The objective of this study was to identify psychosocial factors to explain intentions of children and adolescents with hemophilia to adhere to recommendations for self-care. Twenty-four patients with hemophilia A and B, aged 6–18 years old, and their parents, completed a survey. Measures assessed factors from the theory of planned behavior, physical activity, and medical treatment adherence. The results indicate that past behaviors, attitudes, and subjective norms explained a large proportion of the intention to engage in future nonrecommended physical activity. This study supports the need to investigate motivational factors underlying behaviors in larger scale studies and identifies targets for future interventions.